2011
DOI: 10.1111/j.1365-2648.2011.05838.x
|View full text |Cite
|
Sign up to set email alerts
|

Decision‐making processes used by nurses during intravenous drug preparation and administration

Abstract: Implications for practice included: exploring new and effective methods of education based on behavioural theories; involving staff in updating policies and procedures; formal assessment of staff during intravenous preparation and administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 46 publications
2
57
0
1
Order By: Relevance
“…Empirical evidence on workarounds arises predominantly from studies conducted in acute care settings in the United States of America (USA) (n=29). The United Kingdom (UK) (n=8) [34-41], Australia (n=5) [42-46], The Netherlands (n=5) [47-51], Canada (n=3) [52-54], Japan (n=1) [55], Lebanon (n=1) [56] and Thailand (n=1) [57] also hosted studies examining workarounds. Additionally, four studies were conducted in both Canada and the USA [1,24,58,59] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical evidence on workarounds arises predominantly from studies conducted in acute care settings in the United States of America (USA) (n=29). The United Kingdom (UK) (n=8) [34-41], Australia (n=5) [42-46], The Netherlands (n=5) [47-51], Canada (n=3) [52-54], Japan (n=1) [55], Lebanon (n=1) [56] and Thailand (n=1) [57] also hosted studies examining workarounds. Additionally, four studies were conducted in both Canada and the USA [1,24,58,59] (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Other justifications included a perception that rules and policies are not always in the best interest of the patient [36,42,66], the importance of customising care to the need of patients [4,6,42,72,84], patient isolation [4,68,84] and unavailability [6,34] and concern about the impact of adhering to policy on patients’ perceptions (e.g. wearing gowns, gloves and masks [57] and repeatedly checking patient identification [41]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a context where nurses are largely responsible for the preparation and handling of parenteral medication in hospital settings [6, 18–20], it is important to work on their perceptions since these perceptions can influence their willingness to follow current recommendations on the issue [21], including the use of filter needles in their practice.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12][13][14][15][16][17][18] There was one prospective study identified through the literature review, this paper described the frequency of medication administration and prescription errors in ED. 13 It was identified that 60% of patients had one or more medication errors (178 errors in 192 patients) and 37% of medication errors reached the patient.…”
Section: Introductionmentioning
confidence: 99%